Contemporary Approaches to Treating and Preventing Acid-Dependent Digestive Tract Disorders in Patients with Ischemic Heart Disease - Ortiq o’g’li, Raupov Abdurahmon (Journal of Innovation in Education and Social Research, 2025)
This article emphasizes the problems of comorbidity between ischemic heart disease and acid-dependent gastrointestinal disorders in patients. The role of inflammation, metabolic imbalance, pharmaceutical interactions, common risk factors, and pathophysiological relationships are examined. It is proven that contemporary therapy and prevention strategies, such as the use of proton pump inhibitors, cytoprotectors, and Helicobacter pylori elimination, are beneficial. In order to maximize the clinical management of patients with comorbid diseases, the article offers suggestions.